Republic of Tajikistan : 2017 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2021)
Tajikistan is the poorest of the eight Central Asian and Caucasus countries. Economic growth has been high and funded by inward remittances, but poverty remains significant. Macroeconomic policies were generally prudent before the external shocks (lower oil and commodity prices and weaker growth in trading partners) in 2015-16, but slow progress in structural reforms constrained diversification and employment generation. External shocks (through lower remittances and currency depreciation) and an inadequate policy response weakened the external position, exposed major weaknesses in the banking system, and contributed to a rise in public debt. Program discussions held in 2016 were not concluded. While the authorities launched a bank recapitalization plan in December 2016 to maintain depositor confidence and financial stability, additional banking sector reforms are needed.